The Welfare State and Higher Education on Their Way Towards Privatisation. Global and Transition Economies’ Perspectives - Kwiek, Marek (My University, 2007)
The general theme of coping with financial austerity has been very much visible in thinking about the future of both welfare state and (public) higher education, and it has often been accompanied by its twin theme in thinking about the future of social services, namely privatisation. The tight fiscal environment for both the welfare state in general and for higher education in particular continues, and in many countries is even bound to intensify. In European transition countries, the solutions suggested to higher education systems increasingly include references to such notions as academic entrepreneurialism (in both teaching, research, and third mission activities), financial self-reliance of academic institutions, and costsharing (the introduction, or increasing, tuition fees, smaller state subsidies, more student land and less scholarships etc. What is suggested is also bigger workloads for academics and bigger classes for students, contracts for faculty instead of tenure etc. Higher education is no longer isolated from the society and, especially, the economy, its (especially research) funding is no longer guaranteed and its missions are under scrutiny. The solutions suggested are both cost-side and revenue-side, strongly relating the future of public higher education to current financial austerity. Consequently, university missions are being renegotiated, either in theory or in practice (or both), new economic contexts of public universities are increasingly important, following renewed interest in higher education, and new concepts in rethinking higher education are being coined by international and supranational organizations.
Keywords: privatization; higher education; welfare state; postwar welfare contract; social contract; permanent austerity; Central Europe; public funding; higher education policy; welfare policy; welfare state in transition; transition economies; globalization; global pressures; welfare programs; competing welfare services; public services; competition